2020
DOI: 10.1136/jitc-2019-000471
|View full text |Cite
|
Sign up to set email alerts
|

Performance of anti-CD19 chimeric antigen receptor T cells in genetically defined classes of chronic lymphocytic leukemia

Abstract: BackgroundWhile achieving prolonged remissions in other B cell-derived malignancies, chimeric antigen receptor (CAR) T cells still underperform when injected into patients with chronic lymphocytic leukemia (CLL). We studied the influence of genetics on CLL response to anti-CD19 CAR T-cell therapy.MethodsFirst, we studied 32 primary CLL samples composed of 26 immunoglobulin heavy-chain gene variable (IGHV)-unmutated (9ATM-mutated, 8TP53-mutated, and 9 without mutations inATM,TP53,NOTCH1orSF3B1) and 6IGHV-mutate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 40 publications
0
13
0
Order By: Relevance
“…CAR T cell preparation, quality assessment and in vivo studies were previously described. 15 Briefly, T cells were isolated from buffy coats of healthy donors purchased from the Department of Transfusion and Tissues of University Hospital Brno using the RosetteSep Human T cell enrichment Cocktail (StemCell). Immediately following isolation, T cells were activated using IL-2 (50 U/mL; Miltenyi Biotec) and Dynabeads Human T-activator CD3/CD28 (ratio 1:3 bead:cell; ThermoFisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…CAR T cell preparation, quality assessment and in vivo studies were previously described. 15 Briefly, T cells were isolated from buffy coats of healthy donors purchased from the Department of Transfusion and Tissues of University Hospital Brno using the RosetteSep Human T cell enrichment Cocktail (StemCell). Immediately following isolation, T cells were activated using IL-2 (50 U/mL; Miltenyi Biotec) and Dynabeads Human T-activator CD3/CD28 (ratio 1:3 bead:cell; ThermoFisher Scientific).…”
Section: Methodsmentioning
confidence: 99%
“…This may be partially remedied by concurrent ibrutinib treatment, which is known to cause an efflux of tumor cells from the tissue compartments into the blood [ 61 ]. Additionally, some preclinical evidence exists showing that TP53 -mutated CLL gives rise to early disease onset, high tumor burden, and inefficient T-cell engraftment in a mouse model, leading to inferior performance of anti-CD19 CAR T cells [ 62 ]. When we closely inspected patient lists from anti-CD19 clinical trials ( Table 1 ), only 3 of 20 cases unequivocally bearing del17p ( TP53 genetic locus) reached complete remissions.…”
Section: Determinants Of Clinical Response and Treatment Resistancementioning
confidence: 99%
“…In contrast to CD19-CAR T cells that only targeted CD19 + leukemic cells, the bispecific CD19/CD20-CAR T cells also eradicated all leukemic cells, even those that lost CD19 expression at the surface in a xenograft NSG model [ 86 ]. Interestingly, anti-CD19 CAR T cell therapy was evaluated in a B-CLL xenograft mice model by injecting into mice B cell lines carrying individual KOs representative for the mutational landscape in B-CLL [ 87 ]. In vivo, they confirmed that anti-CD19 CAR T cells prolonged survival of the different genetic classes of B-CLL tumor cells and revealed a differential anti-tumor efficacy according to the mutation introduced [ 87 ].…”
Section: Preclinical Evaluation Of Car T and Car Nk Cell Therapiesmentioning
confidence: 99%
“…Interestingly, anti-CD19 CAR T cell therapy was evaluated in a B-CLL xenograft mice model by injecting into mice B cell lines carrying individual KOs representative for the mutational landscape in B-CLL [ 87 ]. In vivo, they confirmed that anti-CD19 CAR T cells prolonged survival of the different genetic classes of B-CLL tumor cells and revealed a differential anti-tumor efficacy according to the mutation introduced [ 87 ]. This emphasizes the need for more personalized and optimized CAR design in treatment of B-CLL.…”
Section: Preclinical Evaluation Of Car T and Car Nk Cell Therapiesmentioning
confidence: 99%